160k views
4 votes
What is the average rate of change for h(x)=x^2+x-6

User Jeronimo
by
5.1k points

1 Answer

6 votes


\bf slope = m = \cfrac{rise}{run} \implies \cfrac{ f(x_2) - f(x_1)}{ x_2 - x_1}\impliedby \begin{array}{llll} average~rate\\ of~change \end{array}\\\\[-0.35em] \rule{31em}{0.25pt}\\\\ h(x)=x^2+x-6 \qquad \begin{cases} x_1=0\\ x_2=3 \end{cases}\implies \cfrac{h(3)-h(0)}{3-0} \\\\\\ \cfrac{(3^2+3-6)~~-~~(0^2+0-6)}{3}\implies \cfrac{(6)-(-6)}{3} \\\\\\ \cfrac{6+6}{3}\implies \cfrac{12}{3}\implies 4

User Mediocre Gopher
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.